2021
DOI: 10.3389/fpsyg.2021.584565
|View full text |Cite
|
Sign up to set email alerts
|

Patients and Parents’ Experience of Multi-Family Therapy for Anorexia Nervosa: A Pilot Study

Abstract: Background: Family therapy is considered as the gold standard in treatment of adolescents with anorexia nervosa (AN). Among the different types of family therapy, multi-family therapy (MFT) is increasingly used for treating AN, and shows promising results. In this article, our focus relied on the patients’ and their parents’ perceptions of the effectiveness and the underlying mechanisms of the MFT. Methods: The present pilot exploratory qualitative study included two focus groups conducted using a semi-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…As a point of difference, participants in this study did not mention any unhelpful aspects of the inevitable comparisons that occur between participants in the group. This has been reported by some participants, particularly parents, who receive MFT-AN in other studies [ 24 ]. Similarly, participants in MFT-AN studies have not identified wanting to be challenged more in group, as was the case in this study.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…As a point of difference, participants in this study did not mention any unhelpful aspects of the inevitable comparisons that occur between participants in the group. This has been reported by some participants, particularly parents, who receive MFT-AN in other studies [ 24 ]. Similarly, participants in MFT-AN studies have not identified wanting to be challenged more in group, as was the case in this study.…”
Section: Discussionsupporting
confidence: 73%
“…The current findings are broadly consistent with previous research on MFT for adolescent eating disorders [ 19 ]. This literature highlights the group as place of support and learning associated with symptom change [ 21 24 ]. As a point of difference, participants in this study did not mention any unhelpful aspects of the inevitable comparisons that occur between participants in the group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all studies, there was a common finding that MFT is experienced as both helpful and challenging with similar experiences described for adults and young people for both MFT‐AN and MFT‐BN. From data generated through observation, interviews and focus groups collected during and after treatment, there was a sense by most participants that MFT helped the family to view the eating disorder symptoms in new ways (Baumas et al, 2021 ; Duarte, 2012 ; Salaminiou, 2005 ; Voriadaki, Simic, Espie, & Eisler, 2015 ), take on new perspectives (Duarte, 2012 ; Engman‐Bredvik et al, 2016 ; Tantillo et al, 2015 ;Whitney, Currin, et al, 2012 ; Wiseman et al, 2019b ), gain new skills (Duarte, 2012 ; Tantillo et al, 2015 ) and feel more empowerment (Engman‐Bredvik et al, 2016 ; Salaminiou, 2005 ). Together, this helped people, particularly parents/caregivers, feel less guilty, scared, and anxious (Whitney, Currin, et al, 2012 ) and feel more confident (Whitney, Currin, et al, 2012 ; Wiseman et al, 2019b ).…”
Section: Resultsmentioning
confidence: 99%
“…A common theme across several studies was that MFT led to a shift in the quality of family connection and dynamics (Baumas et al, 2021 ; Berit Støre Brinchmann & Krvavac, 2021 ; Duarte, 2012 ; Tantillo et al, 2015 ; Wiseman et al, 2019b ). Commonly, parents/caregivers felt MFT provided a new support network that helped people in all family roles feel less alone and isolated (Duarte, 2012 ; Engman‐Bredvik et al, 2016 ; Salaminiou, 2005 ; Tantillo et al, 2015 ; Wiseman et al, 2019b ), which was also echoed by some patients, albeit fewer (Duarte, 2012 ; Salaminiou, 2005 ).…”
Section: Resultsmentioning
confidence: 99%